State of catecxolaminergine systems of the brain in forming of sydnocarb psychosis - Al Nasir Eiad; Kharaponova H.B.; Alnukari Abdul Karim; Demchenco H.N.; Drozdov A.L. (Medičnì Perspektivi)
Violations of mnestic reactions are one of substantial signs of disorders of nervous activity. On the basis of it, as a criterion of forming of experimental psychosis, in our supervisions, the state of processes of conditionally-reflex memory was studied in rats. To cover up mechanisms of derangements of conditionally reflex activity in the process of forming of psychotic symptomatic complex, maintenance of adrenalin, noradrenalinum and neurospecific albumen S - 100 in the brain structures, that take a direct part in the processes of memory was studied. Derangements of cognitive function, that are the result of neurotoxic action of sydnocarb, are related to reduction of maintenance of noradrenalinum in the frontal cortex, as well as adrenalin in the pons varolii. That is, sydnocarb psychosis is accompanied by reduction of activating role of the cortex and trunk structures, negatively affecting the state of mnestic reactions. In the hippocampus and striate body excitation causes violation of memory processes and on the contrary, concentration of noradrenalinum rose. Thus, the presented model of experimental psychosis, created by subacute introduction of sydnocarb, is an adequate and alternative methodology of psychotic disorders forming in animals resulted from direct participation of the catecholaminergetic systems of CNS.